'It's easy to say "don't sign anything"': Debt problems among recent migrants from a non-English-speaking background. (June 2019) - Bourova, Evgenia; Ramsay, Ian; Ali, Paul
Legal protections are in place to allow Australians in financial hardship to avoid negative credit ratings and bankruptcy by negotiating alternative payment arrangements with creditors. This article draws upon focus groups with consumer advocates to investigate whether these protections are meeting the needs of recent migrants from a non-English-speaking background. The authors argue that recent migrants receive inadequate support with the financial aspects of settlement in Australia, creating barriers to the resolution of debt problems. They recommend measures that could reduce the vulnerability of recent migrants in consumer transactions and assist them to resolve debt problems before they escalate.